Երկբարբառացումը որպես քերականական միջոց հայերենի որոշ բարբառներում - Բառնասյան, Ջեմմա (ՀՀ ԳԱԱ ԼԻ հրատ.)
The prevailing part of the Armenian dialects is not characterized by diphthongs and triphthongs. We are convinced of this while carrying out 28 collection works with the Armenian dialects. For Armenian dialects the usage of simple vowels and diphthongs is most characteristic, as, for example, in the current largest - Ararat dialect, where all diphthongs and triphthongs of ancient Armenian have undergone a phonetic change. Dialectologist A. Gharibyan studied and appreciated the interesting reality of the transformation of diphthongization into a grammatical means, such as the grammatical means of transition from an indefinite gender of a noun to a definite gender in the dialects of Kesab, Qabusie in Syria. The famous linguist A. Acharyan believes that the diphthongization of simple vowels in the Agulis dialect does not have a deep antiquity, it is a relatively new phenomenon, which is noticeable by the stratification of various phenomena of phonetic changes. Преобладающей части диалектов армянского не характерны дифтонги и трифтонги. В этом мы убеждаемся при осуществлении коллекционных работ с армянскими диалектами. Для армянских диалектов наиболее характерно использование простых гласных и дифтонгов, как, например, в нынешнем крупнейшем - Араратском диалекте, где все дифтонги и трифтонги древнеармянского претерпели фонетическое изменение. Диалектолог А. Гарибян изучил и оценил интересную реальность превращения дифтонгизации в грамматическое средство, как, например, грамматическое средство перехода от неопределенного рода существительного к определенному роду в диалектах Кесаба, Кабусие в Сирии. Известный лингвист А. Ачарян считает, что дифтонгизация простых гласных в агулисском диалекте не имеет глубокой древности, это относительно новое явление, что заметно по расслоению различных явлений фонетических изменений.
Keywords: Բարբառագիտություն